(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
Law and economics is an interdisciplinary study method that combines law and economics. In general terms, its research seeks to identify the economic reflexes generated by a given rule, judicial decision or other legal element and vice versa, in other words, the effects to be created in the legal field from any economic situation. In fact, the observable hypotheses are as varied as possible, and it is possible to approach almost the entire legal-normative spectrum (e.g. civil, commercial, criminal, tax, administrative, environmental law, etc.). Thus, given that all taxes are levied on a fact or situation that represents a certain economic measure (e.g. earning income, owning goods, circulating goods, transferring goods to third parties inter vivos or causa mortis, finalizing a financial transaction, etc.), tax events can be classified as taxable events. ), tax events can be of great interest to Law and Economics, especially in relation to the results arising from the tax system (e.g. taxpayer reaction, income distribution, induction or inhibition of economic activity, potentially collectible volumes, etc.), although there are still few studies that pursue this interdisciplinary approach in the tax field.